Conventional versus epineural sleeve neurorrhaphy technique: Functional and histomorphometric analysis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2002)
Three methods of nerve repair involving the epineural sleeve technique were compared with conventional nerve repair using the rat sciatic nerve transection model in four groups. In group 1, the sciatic nerve was repaired using the conventional epineural technique by placing four sutures. In groups 2, 3, and 4, the epineural sleeve technique was combined with two sutures, fibrin glue, and two sutures with fibrin glue, respectively. Functional recovery was evaluated using walking track analysis, limb circumference, and the severity of toe contracture. Diameter of the sciatic nerve fibers, total number of myelinated fibers, diameter of the myelin sheath, and the axon-to-fiber diameter ratio were measured at 12 weeks. The results showed better functional recovery as well as a higher number of myelinated fibers in groups using the epineural sleeve technique compared with conventional technique (p < 0.05). The addition of fibrin glue, however, did not make any significant difference. The epineural sleeve technique was found to be superior when compared with conventional nerve repair, providing faster functional recovery and improved nerve regeneration.
Keywords: NERVE; REGENERATION